DISASTER PREPAREDNESS AND AGE-FRIENDLY CITIES AND COMMUNITIES: AN OPPORTUNITY TO IMPACT COMMUNITY RESILIENCE. (11th November 2018) - Gibson, A; Fletcher, P; Helen McSweeney-Feld, M
Abstract: The World Health Organization's (WHO) Age-Friendly Cities and Communities program has provided international guidelines to help communities prepare for rapid population aging and the parallel trend of urbanization (2007). In the U.S., there are over 200 communities with a commitment to developing age-friendly environments and appropriate, affordable housing for those over 60. Developing community resilience, or the focus of enhancing communities to reduce the negative impacts of disasters, greatly supports older adults' well-being within our communities. Community resilience expands the traditional preparedness approach by encouraging actions that build preparedness while also promoting strong community systems and addressing the many factors that contribute to health. This paper explores the potential to prepare for the needs of older adults affected by disaster considering the role of community resilience and gerontological disaster planning within Age-Friendly Cities and Communities' strategic plans. Presentation will propose recommendations and examples from communities already implementing such practices.